Sustainable Green University: Waste Auditing, German Jordanian University as a Case Study - Hindiyeh, Muna; Jaradat, Mustafa; Albatayneh, Aiman; Alabdellat, Batool; Al-Mitwali, Yazan; Hammad, Bashar (Frontiers in Built Environment, 2022)
In order to get on the path of sustainable development as a society as a whole, a great transformation is required. Universities are embedded in society and networked with it through various forms of interaction; they influence social discourses and often have a decisive influence on them. As educational institutions, universities have to take a critical stance on the state of our earth and actively fulfill their responsibility. The German Jordanian University (GJU), like any other university, produces solid and hazardous waste. A waste audit was done to identify the waste streams and the opportunities for reinforcing waste reduction, recycling, and composition while enhancing the comprehensive sustainability of a waste management program. The results showed that an average of 2,500 kg of waste was produced per week. The composition of the waste generated at the GJU main campus was 1,051 kg (41%) for paper and cardboard, 875 kg (35%) for plastics, 325 kg (13%) for biowaste, and 275 kg for other wastes. The performed UI GreenMetric showed high potential in the programs to reduce the use of paper and plastic on campus and the treatment of toxic waste with a score of 75 points. The results of this study indicate high potential in the recycling program for university waste, organic and inorganic waste treatment, and sewage disposal. The results for these indicators were moderate, a score of 75 points out of 300 points. Thus, more focus and actions should be placed on these indicators to enhance a sustainable green campus.